Tracing Interlanguage through Grammatical Errors: An Analysis of Indonesian–English Translation by Junior High School Students - Arsai, Alfons Napoleon; Arsai, Almendita Flora Wendelmood (Jurnal Tahuri, 2024)
This study examines grammatical errors in Indonesian–English translation by junior high school students to trace interlanguage development during second language acquisition. In Indonesian EFL classrooms, grammatical errors persist as a key learning challenge, reflecting both limited linguistic mastery and the evolving interlanguage system in learners’ cognition. This mixed-method research integrates error analysis and interlanguage theory, involving 28 eighth-grade students who completed a short translation task followed by interviews. Errors were analyzed using the Surface Strategy Taxonomy, covering omission, addition, misformation, and misordering, and subsequently quantified and interpreted linguistically. Findings show that misformation and omission errors dominate, indicating transitional interlanguage stages shaped by literal translation strategies and structural transfer from Indonesian. The study highlights the cognitive and sociolinguistic factors influencing learners’ interlanguage, including instructional input and habitual language use. Its novelty lies in systematically linking grammatical errors in translation with interlanguage development at the junior high school level in Indonesia, an underexplored context. The study contributes to applied linguistics by extending interlanguage and error analysis frameworks to a Southeast Asian setting and offers pedagogical insights for grammar and translation instruction. Teachers are encouraged to design interlanguage-sensitive remedial strategies addressing dominant error types and bridging structural differences between Indonesian and English.